Screening utility and acceptability of the Kiswahili-pGALS (paediatric Gait, Arms, Legs, Spine) at a tertiary referral hospital in Kenya-A diagnostic accuracy study - Jacqueline E. Kawishe; Anthony Ngugi; Stanley Luchters; Helen Foster; Angela Migowa (BMC, 2023)
Abstract Background Paediatric rheumatic diseases cause considerable disease burden to children and their families (Moorthy LN, Peterson MGE, Hassett AL, et al, Pediatric Rheumatology 8:20, 2010). Delayed diagnosis is a significant determinant of severity and mortality attributed to these conditions (Foster HE, Eltringham MS, Kay LJ, et al, Arthritis Care Res 57(6):921-7, 2007). pGALS is a simple clinical tool used to assess joints and identify musculoskeletal (MSK) conditions in school-going children to enable early referral to paediatric rheumatologists. Objectives This study aimed to translate and determine the diagnostic accuracy and acceptability of a Kiswahili version of the pGALS screening tool among Kiswahili-speaking children. Methods The pGALS screening questions were translated into Kiswahili according to the World Health Organisation (WHO) standard for translation of a tool. The validity of the Kiswahili PGALS was ascertained and acceptability rated (time taken, discomfort). Using systematic random sampling, we enrolled children aged 5-16 years presenting at the Aga Khan University Hospital's (AKUH) emergency department in Kenya, who spoke Kiswahili and had symptoms suggestive of an MSK condition. Those already under follow-up at the paediatric rheumatology service at AKUH were excluded. MSK assessment was undertaken by two resident doctors using the newly translated Kiswahili-pGALS and findings were compared with a paediatric rheumatologist examination ('gold-standard') on the same day, and who was blinded to the pGALS findings. We analysed demographic details of the participants and determined the diagnostic accuracy by cross tabulation of the index test results by the results of the reference standard. Results One hundred children with a median age of nine years (IQR 7-11) were enrolled. The sensitivity and specificity of the Kiswahili-pGALS screening tool were 76.8% (95%CI 63.6-87.0%) and 40.0% (95%CI 23.9-57.9%), respectively. The diagnostic accuracy was 62.7% (95%CI 52.1-72.1%), area under the ROC was 0.58 (95%CI 0.48-0.68). The median time to perform the Kiswahili-pGALS was 5.0 min (IQR 3.5-6.0 min). Ninety percent of the guardians found the practice of Kiswahili-pGALS to have none, or only some discomfort. Conclusions The Kiswahili-pGALS's was found to be a useful screening tool to aid early identification of MSK conditions in Kiswahili-speaking settings. However, the low specificity implies that relatively large number of false positives would still need to be reviewed by a rheumatologist if the tool is adapted for use.